2003
DOI: 10.1051/0004-6361:20021802
|View full text |Cite
|
Sign up to set email alerts
|

Non-LTE abundances of magnesium, aluminum and sulfur in OB stars near the solar circle

Abstract: Abstract. Non-LTE abundances of magnesium, aluminum and sulfur are derived for a sample of 23 low-v sin i stars belonging to six northern OB associations of the Galactic disk within 1 kpc of the Sun. The abundances are obtained from the fitting of synthetic line profiles to high resolution spectra. A comparison of our results with HII region abundances indicates good agreement for sulfur while the cepheid abundances are higher. The derived abundances of Mg show good overlap with the cepheid results. The alumin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 15 publications
5
20
3
Order By: Relevance
“…This new determination of the oxygen abundance in the Sun is consistent with the abundance obtained in B and late O stars (Daflon et al 2003), solving the problem of the Sun being more oxygen-rich than the ISM. Nevertheless, the depth of the solar convection zone computed with the new solar abundance lines errors due to blends with Ni i and CN lines are considered.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This new determination of the oxygen abundance in the Sun is consistent with the abundance obtained in B and late O stars (Daflon et al 2003), solving the problem of the Sun being more oxygen-rich than the ISM. Nevertheless, the depth of the solar convection zone computed with the new solar abundance lines errors due to blends with Ni i and CN lines are considered.…”
Section: Discussionsupporting
confidence: 81%
“…2 This value was supported by the impressive agreement between the abundance obtained from the [O i] lines (Lambert 1978; A O ¼ 8:92 dex) and the pure rotation ; A O ¼ 8:91 dex) and fundamental vibration-rotation OH lines ; A O ¼ 8:93 dex). That solar oxygen abundance (A O ¼ 8:9) is high when compared to the abundance of nearby young OB stars (e.g., Daflon et al 2003; A O ¼ 8:6 8:7 dex). Considering that the Sun is about 4.6 Gyr old, its oxygen abundance is supposed to be lower than or equal to that of the present day interstellar medium (ISM).…”
Section: Introductionmentioning
confidence: 89%
“…We find a mean abundance of log (Mg) = 7.21 ± 0.07. This is 0.46 dex lower than the mean value found by Lyubimkov et al (2005) and 0.16 dex lower than that found by Daflon et al (2003) for OB stars in the solar circle. The components of V615 Per have a subsolar Mg abundance and resemble halo B stars more than nearby examples (Daflon et al 2004).…”
Section: Application To V615 Perseicontrasting
confidence: 63%
“…Radial-velocity standard stars were not observed. (The adopted linelists can be found in Daflon et al 2001Daflon et al , 2003 We inspected and identified all unblended lines visible in the spectral range between 3798 Å (H i) and 7065 Å (He i) in each target star: the number of measurable lines varied between 10 and 74, depending on the star spectral type, rotation velocity, possible multiplicity, but also on the signal-to-noise of the obtained spectra. (We note, however, that for the double lined binary HD 133242, it was possible to measure positions only for 4 lines in component A and 6 lines in component B.)…”
Section: Analysis and Discussionmentioning
confidence: 99%